Molecular Remodeling in Populus PdKOR RNAi Roots Profiled Using LC‐MS/MS Proteomics. Issue 24 (7th October 2020) - Abraham, Paul E.; Matthiadis, Anna; Hettich, Robert L.; Kalluri, Udaya C.
Abstract: Plant endo‐β‐1, 4‐glucanases belonging to the Glycoside Hydrolase Family 9 have functional roles in cell wall biosynthesis and remodeling via endohydrolysis of (1→4)‐β‐d ‐glucosidic linkages. Modification of cell wall chemistry via RNA interference (RNAi)‐mediated downregulation of Populus deltoides KORRIGAN (PdKOR), an endo‐β‐1, 4‐glucanase familygene was shown to have functional consequences on the composition of secondary metabolome and the ability of modified roots to interact with beneficial microbes. The molecular remodeling that underlies the observed differences at metabolic, physiological, and morphological levels in roots is not well understood. Here a liquid chromatography (LC)‐tandem mass spectrometry (MS/MS)‐based proteome profiling approach is used to survey the molecular remodeling in root tissues of PdKOR and control plants. A total of 14316 peptides are identified and these mapped to 7139 P. deltoides proteins. Based on 90% sequence identity, the measured protein accessions represent 1187 functional protein groups. Analysis of Gene Ontology (GO) categories and specific individual proteins show differential expression of proteins relevant to plant‐microbe interactions, cell wall chemistry, and metabolism. The new proteome dataset serves as a useful resource for deriving new hypotheses and empirical testing pertaining to functional roles of proteins and pathways in differential priming of plant roots to interactions with microbes.